NKX6.3 modulation of mitotic dynamics and genomic stability in gastric carcinogenesis - Jung Hwan Yoon; Jeong-Kyu Kim; Jung Woo Eun; Hassan Ashktorab; Duane T. Smoot; Suk Woo Nam; Won Sang Park (Cell Communication and Signaling)
Abstract Background Gastric cancer remains a significant global health challenge, characterized by poor prognosis and high mortality rates. Mitotic integrity and genomic stability are crucial in maintaining cellular homeostasis and preventing tumorigenesis. The transcription factor NKX6.3 has emerged as a potential regulator of these processes in gastric epithelial cells, prompting an investigation into its role in gastric cancer development. Methods We employed a combination of in vitro and in vivo techniques to elucidate the impact of NKX6.3 depletion on mitotic dynamics and genomic stability in gastric epithelial cells. Quantitative real-time PCR and Western blot analyses were conducted to assess the expression of mitosis-related genes and proteins. Flow cytometry was utilized to evaluate cell cycle distribution, while immunofluorescence microscopy enabled the visualization of mitotic abnormalities. Statistical analyses, including Student’s t-test and ANOVA, were performed to determine the significance of our findings. Results Our results demonstrate that NKX6.3 depletion leads to significant mitotic defects, characterized by increased chromosome misalignment and lagging chromosomes during anaphase. These abnormalities corresponded with elevated levels of genomic instability markers, indicating compromised genomic integrity. Furthermore, the loss of NKX6.3 resulted in altered expression of key regulatory proteins involved in mitosis and DNA repair pathways, suggesting a mechanistic link between NKX6.3 and the maintenance of genomic stability in gastric epithelial cells. Depletion of NKX6.3 resulted in accelerated cell cycle progression and the formation of abnormal mitotic figures, leading to genomic instability characterized by increased DNA content and structural abnormalities. In both in vitro and xenograft models, the depletion of NKX6.3 significantly upregulated AurkA and TPX2, which correlated with gains in DNA copy number. An inverse relationship was observed between NKX6.3 expression and the levels of AurkA and TPX2 in human gastric cancer tissues. Conclusions This study highlights the essential role of NKX6.3 in regulating mitotic integrity and genomic stability in gastric carcinogenesis. The findings suggest that targeting NKX6.3 may offer a novel therapeutic strategy for improving treatment outcomes in gastric cancer by restoring mitotic fidelity and genomic stability. Trial registration This study was not registered.